Electrothermal Actuators with Ultrafast Response Speed and Large Deformation. (25th May 2020) - Chen, Guinan; Yang, Zhonglin; Wang, Wenwen; Bi, Lili; Chen, Liangjun; Peng, Yongwu; Ye, Changhui
Abstract : The ability to fabricate electrothermal actuators (ETAs) simultaneously featuring ultrafast response speed (within 0.1 s), large deformation (bending for at least 360°), high figure‐of‐merit (FoM, larger than 0.1%), and low driving voltage (smaller than 1 V) in a single device is extremely important and challenging for their applications in artificial muscles, switches, and microsensors for robotics and biomimetic devices. Herein, an ETA composed of a silver nanowire (AgNW) layer and an ultrathin linear low‐density polyethylene (LLDPE) film with all the aforementioned features is designed. Due to the high conductivity of the AgNW layer and the great difference between the coefficients of thermal expansion of AgNW layer and LLDPE film as well as the huge change in the heat transfer coefficient between flat and rolled ETA, the obtained ETA exhibits an ultrafast response speed of 0.08 s for a bending angle of 360° with a FoM of 0.46% at a low driving voltage of 1 V, over one order of magnitude larger than those of reported ETAs. As a proof‐of‐concept application, the as‐prepared ETAs can be used as intelligent mechanical devices with excellent performance. Abstract : An electrothermal actuator (ETA) composed of a silver nanowire (AgNW) layer and an ultrathin linear low‐density polyethylene (LLDPE) film exhibits an ultrafast response speed of 0.08 s for a bending angle of 360° with a FoM of 0.46% at a low driving voltage of 1 V, over one order of magnitude larger than those of reported ETAs.